Pensiones y estratificación social en América Central y las Antillas Mayores. Pensions and social stratification in Central America and the Greater Antilles - Diaz-Tendero Bollain, Aida (Latinoamérica. Revista de Estudios Latinoamericanos, 2017)
El objetivo de este artículo es aplicar el enfoque de la Economía Política del Envejecimiento al estudio de la (in) seguridad económica de las personas mayores en América Central y las Antillas Mayores, el cual considera indicadores como tipo de régimen de bienestar, articulación de la política social a partir de la asistencia y seguridad sociales, cobertura, sistemas de pensiones contributivas y no contributivas a una muestra de nueve países de la subregión (Costa Rica, Cuba, El Salvador, Guatemala, Haití, Honduras, Nicaragua, Panamá, República Dominicana). El hallazgo es que la subregión presenta una gran heterogeneidad respecto del tipo de Estado y régimen de bienestar, y su consiguiente efecto en la seguridad económica de las personas mayores. Abstract: The paper aims at applying the Political Economy of Aging approach to the study of the economic (in) security of the elderly in Central America and the Greater Antilles. This approach studies the role of the State in the reproduction, attenuation or accentuation of inequities that affect older people. Indicators from Political economy such as: kind of welfare regime, articulation of social policy based on assistance and social security, coverage, contributory and non-contributory pension systems were applied to a sample of nine countries of the area (Costa Rica, Cuba, El Salvador, Guatemala, Haiti, Honduras, Nicaragua, Panama and Dominican Republic). The subregion presents a great heterogeneity of kinds of state and welfare regimes and its consequent effect on the economic security of the elderly